Analisis Kesiapan Guru Dalam Pembelajaran IPA di SMP Negeri Bungku Timur - Estin Nursanti Handayani; Mohammad Jamhari; Fatmah Dhafir; Lestari M.P. Alibasyah; Hayyatun Mawaddah; Musdalifah Nurdin (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to analyze the level of teacher readiness in teaching science at Bungku Timur Public Junior High School. The research method used is a qualitative descriptive approach. Research data were collected through observation of learning tools, observation of the learning process, interviews, and documentation. The research subjects involved science teachers from four public junior high schools in the Bungku Timur area. The results showed that (1) the readiness of learning tools, including the education calendar, annual program, semester program, teaching modules, and teaching materials, was in the Ready to Very Ready category, with an achievement percentage ranging from 81.25% to 100%; (2) it was found that two schools had fulfilled all the tools completely, while the other two schools still needed improvement in several components; (3) for the readiness of the learning process, the aspects of teachers' knowledge, attitudes, and skills showed excellent results; (4) Teachers have a strong understanding of science material, learning strategies, and student characteristics; (5) Teachers demonstrate high motivation to teach, a positive attitude towards innovation, and good work discipline. In terms of skills, teachers are considered quite skilled in developing learning tools, managing media, and implementing active learning, with a rating of “Ready”.